Ketersediaan dan Perilaku Konsumsi Makanan Jajanan dengan Status Gizi pada Anak Sekolah Dasar - Himatul Muhimah; Farapti Farapti (Media Gizi Kesmas, 2023)
Background: The nutrition problem in school-age children is still a major concern in almost all the world. Epidemiological studies show that the availability of high-energy snack foods, high levels of fat, sugar and sodium are closely related to the increased risk of the occurrence of nutrition problems, especially over nutrition. Objectives: The purpose of this review literature is to describe the relationship between the availability and consumption behavior of snack foods and how they contribute to nutritional status. Methods: The method uses in writing this literature review is to review international journal articles taken from various sorces such as Medline NCBI, Embase, Google Scholar with a critical appraisal process. Discussion: The result of the average eating behavior for school children depends on the available food availability. Consumption of energy-dense foods such as foods and beverages that are high in calories, high in fat, high in sugar tend to experience an increase in calories and cause overnutrition or obesity. Conclusions: Intervention is needed through nutrition education related to children's eating consumption behavior and monitoring of snack foods available at school.